1983
DOI: 10.1148/radiology.146.3.6828687
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided percutaneous biopsies of head and neck masses.

Abstract: Six patients underwent CT-guided percutaneous pharyngeal or laryngeal biopsies. A retromandibular approach was used in five of these patients. Accurate cytologic information was obtained in all six cases, and no complications were encountered. This technique can be helpful in certain clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The earliest observations suggesting that hypoxia could be measured in this disease were based on the use of polarographic needle electrodes 18 . Almost all of the HNSCC patients studied with this technique had measurements made in enlarged draining lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest observations suggesting that hypoxia could be measured in this disease were based on the use of polarographic needle electrodes 18 . Almost all of the HNSCC patients studied with this technique had measurements made in enlarged draining lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…An early study of in vivo hypoxia was performed with polarographic needle electrodes in enlarged, squamous cell carcinoma-containing neck lymph nodes 18 . This work demonstrated that hypoxia could be measured in a minimally invasive manner and that the resulting values were correlated with short-term treatment response 19 .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] More recently, experience with image-guided FNA of nonpalpable abdominal and thoracic lesions has been applied in the head and neck region. 15 Using a technique described in previous reports, 4,5 lesions arising in the pericarotid sheath, thyroid gland, skull base, and parapharyngeal, parotid/ submandibular, paratracheal, paraesophageal, paraspinal, and infratemporal regions have been sampled under CT guidance at our institution.…”
Section: Commentmentioning
confidence: 99%
“…In our study of 67 tumors in the parapharyngeal space, exact classifi cation of the lesion was possible in 92.5% cases with no false positive report or complication. The diagnostic accuracy of various head and neck tumors by cytology including FNAC varies from 80-95% by various authors [9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%